Diasporic Identity in Contemporary Sinophone Literature: The Role of Language and Cultural Elements - Zhao, Zhongqiu (Journal of psycholinguistic research, 2024)
Amidst the contemporary diasporic landscape in Sinophone literature, this research critically examines the nexus of language, culture, and identity. The study aims to analyze literary pieces composed in Sinophone languages across diverse diasporic communities and uncover the impact of language and cultural elements on the articulation and comprehension of diasporic identity. This paper used the following. comparative and typological research, an in-depth analysis of three Sinophonic texts, and contextual analysis. The subject of the study was three texts: The Joy Luck Club (Amy Tan), Balzac and the Little Chinese Seamstress (Dai Sijie), and The Woman Warrior (Maxine Hong Kingston). The results showed that In The Joy Luck Club , language and cultural facets unveil the characters’ dual identity struggles due to living abroad, exemplified through code-switching’s psychological tension. Balzac and the Little Chinese Seamstress utilizes language and cultural details to underscore the significance of preserving heritage within the diaspora, with literary allusions amplifying this endeavor. In The Woman Warrior , language and cultural elements reflect the heroine’s inner conflict as she navigates her dual cultural allegiance. This scholarly revelation deepens comprehension of how these aspects influence identity formation in the diaspora. These findings broaden the understanding of Sinophone diasporic literature, spotlighting shared trends in identity portrayal through language and culture. The research has theoretical value for literary, cultural, and anthropological studies and practical significance, potentially informing educational initiatives on diasporic literature and cultural diversity. This study’s outcomes hold relevance for students, researchers, and cultural scholars exploring the role of language and culture in diasporic identity expression.